Politeknik Negeri Ujung Pandang Students’ Perception on the Use of AI in Learning English - Shanty Halim; Nurul Hidjrah Hairuddin (Universitas Islam Negeri Palopo, 2025)
This study investigates students’ perceptions of the use of Artificial Intelligence (AI) applications in learning English at Politeknik Negeri Ujung Pandang. The rapid integration of AI-based tools—such as grammar checkers, translation engines, and conversational chatbots—has transformed language learning practices, yet students’ attitudes and levels of acceptance toward these technologies remain varied. Using a descriptive qualitative approach, data were collected through questionnaires and semi-structured interviews involving diploma-level students from several study programs. The findings indicate that most participants perceive AI as a supportive learning aid that enhances vocabulary acquisition, improves writing accuracy, and increases learning motivation through instant feedback and flexible access to language resources. However, concerns were also identified, including overdependence on automated suggestions, reduced critical thinking in writing tasks, and uncertainty regarding the accuracy and authenticity of AI-generated content. Students emphasized the need for clear guidance from lecturers on ethical and pedagogical use of AI in academic contexts. Overall, the study concludes that AI has significant potential to complement English learning when positioned as an assistive tool rather than a substitute for human instruction. The results highlight the importance of digital literacy, critical awareness, and pedagogically guided integration of AI in higher education language learning environments. Recommendations are offered for educators and curriculum designers to develop balanced strategies for technology-supported language instruction.